Ultrasound sensitivity in screening for developmental dysplasia of the hip in newborns: Retrospective study - Abdullah Kan; Najia Alhojaili; Helal Amalki; Attia Alzahrani; Ibrahium Kutbi; Hatim Alomari; Liza Sallam; Samera yaman (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The aim of this retrospective study was to evaluate the ultrasound sensitivity in screening for developmental dysplasia of the hip (DDH) in newborns. DDH is a common musculoskeletal disorder that can lead to long-term complications if not identified early. Ultrasound has emerged as a promising screening tool, but its sensitivity in detecting DDH remains a topic of interest. Methodology: A retrospective analysis was conducted using medical records of newborns that underwent ultrasound screening for DDH. The inclusion criteria involved newborns with risk factors for DDH and those with abnormal physical examination findings. The ultrasound images were reviewed by experienced radiologists who were blinded to the clinical outcomes. Results: A total of 1000 newborns were included in the study. The ultrasound sensitivity in detecting DDH was reported based on the analysis of the collected data. The sensitivity varied according to the severity of hip dysplasia, with higher rates observed in cases of moderate and severe dysplasia compared to mild cases. Conclusion: This retrospective study reveals the potential of ultrasound as a sensitive screening tool for detecting developmental dysplasia of the hip in newborns. The findings highlight the importance of early detection and intervention to prevent long-term complications associated with DDH. Further prospective studies are warranted to validate these results and provide a more comprehensive understanding of the diagnostic accuracy of ultrasound in DDH screening.